Direct somatic embryogenesis induction in Aspilia Africana (Pers.) C. D. Adams, and assessment of genetic homogeneity and physiology of regenerants - Roggers Gang; Sungyu Yang; Kenneth Happy; Joyce Mudondo; Ariranur Haniffadli; Denis Okello; Yeongjun Ban; Youngmin Kang (Scientific Reports)
Abstract Aspilia africana (Pers.) C. D. Adams is a valuable medicinal plant, and the expanding therapeutic use of the plant due to explosion of human population is causing depletion of its wild population, thus requiring propagation. This study established an effective method for direct somatic embryogenesis in A. africana using leaf explants. We evaluated the effects of exogenous plant growth regulators (PGRs) and some molecules on induction, development, and maturation of somatic embryos. Murashige and Skoog (MS) medium supplemented with 1.0 mg/L benzylaminopurine (BAP) and 3.472 × 10−2 mg/L adenosine 5-monophosphate (AMP) optimally induced direct somatic embryogenesis in A. africana leaf explants (100% response and 9.50 ± 0.29 somatic embryos per explant). Differentiation and maturation of somatic embryos was enhanced under osmotic stress induced by using 9 g/L gelrite in MS medium augmented with 0.5 mg/L abscisic acid (ABA) and 6.634 × 10−2 mg/L nicotinamide adenine dinucleotide (NAD) (6.27 ± 0.36 globular, 3.40 ± 0.35 heart, 2.60 ± 0.51 torpedo, and 4.73 ± 0.41 cotyledonary). Half strength MS medium containing 0.5 mg/L gibberellin (GA) and 0.1 mg/L naphthaleneacetic acid (NAA) optimally supported germination (31 ± 1.73%) of cotyledonary somatic embryos. Pre-germination treatment of cold (stratification at 4o C) further stimulated somatic embryo germination (60.00%) and their conversion into plantlets (26.67%). After five weeks of acclimatization, the survival rate of somatic embryo derived A. africana plants was 75.00%. Histological observations and flow cytometric analysis confirmed different somatic embryo stages and stability in genome size of regenerated plants, respectively. Moreover, chlorophyll contents and photosynthetic rates were similar between zygotic and somatic embryo derived plants. This method could be employed in mass clonal regeneration, conservation, synthetic seed production, cryopreservation, and genetic improvement of A. africana. Additionally, the system would provide suitable model for investigating molecular, biochemical, and physiological events, which occur at the induction and development of embryogenesis in A. africana.